Growth hormone replacement may influence the biological action of thyroid hormone on liver and bone tissue. (April 2021) - Glynn, Nigel; Halsall, David J.; Boran, Gerard; Cook, Paul; McDermott, John H.; Smith, Diarmuid; Tormey, William; Thompson, Christopher J.; O'Gorman, Donal; McKenna, Malachi J.; Agha, Amar
Abstract: Objective: Growth hormone (GH) replacement alters the peripheral interconversion of thyroxine (T4) and triiodothyronine (T3). However, little is known about the clinical impact of these alterations. We aimed to compare changes observed in the serum T3:T4 ratio with known biological markers of thyroid hormone action derived from different peripheral tissues. Design: We prospectively studied twenty GH deficient men before and after GH replacement in a tertiary referral endocrine center. Serum biochemical measurements included insulin like growth factor-1 (IGF-1), thyroid hormones (free & total T3, free & total T4 and reverse T3) and TSH. Changes in thyroid hormone concentration were compared to alterations in hepatic and bone biomarkers of thyroid hormone action. Results: GH replacement provoked a decline in serum free T4 concentration (−1.09 ± 1.99 pmol/L; p = 0.02) and an increase in free T3 (+0.34 ± 0.15 pmol/L; p = 0.03); therefore, the free T3:free T4 ratio increased from 0.40 ± 0.02 to 0.47 ± 0.02 (p = 0.002). Sex hormone binding globulin (SHBG) level was unchanged. However, a decline in serum ferritin (−26.6 ± 8.5 ng/mL; p = 0.005) correlated with a fall in freeT4. Alterations in lipid profile, including a rise in large HDL sub-fractions and Lp (a) (+2.1 ± 21.1 nmol/L; p = 0.002) did not correlate with thyroid hormone levels. Significant increases were recorded in serum bone turnover markers - procollagen type 1 amino-terminal propeptide +57.4%; p = 0.0009, osteocalcin +48.6%; p = 0.0007; c-terminal telopeptides of type 1 collagen +73.7%; p = 0.002. Changes in bone formation markers occurred in parallel with fluctuations in thyroid hormone. Conclusion: GH-induced alterations in the thyroid axis are associated with complex, tissue specific effects on thyroid hormone action. Modulation of bone turnover markers suggests that GH may improve the biological action of thyroid hormone on bone. Highlights: Growth hormone modulates peripheral action of thyroid hormone in several tissues including liver and bone. Replacement of growth hormone may improve the biological action of thyroid hormone in bone. Alteration of thyroid hormone metabolism by growth hormone therapy may induce a more hypothyroid hepatic phenotype